A GESTÃO DA EQUIPE MULTIDISCIPLINAR DE SAÚDE EM ORGANIZAÇÕES HOSPITALARES - Silva, Lucimara Alves (2011)
This study attempts to show a correlation between multidisciplinary team management and health care assistance in hospital organizations. Its relevance resides in the fact that this study is moving toward new conceptions that meet contemporary health care challenges. Besides that, it lines up with the decision of Sistema Único de Saúde (SUS) - Unified Health System, Brazil s publicly-funded health care system - considering it as one of its basic principles. Therein, it was inquired: How multidisciplinary health team work and management are developed in hospital organizations? Therefore, it was developed a research whose main objective is to make evident the correlation between multidisciplinary team management and health care assistance. This study s theoretical background relies on the following subject matter: hospital organizations, team work, health care activities peculiar issues, health care and multidisciplinary health care team work. The present study was applied to professionals pursuing a University degree and who belonged to multidisciplinary health care teams from two hospitals: a private one and a philanthropic one, both located at the city of Salvador, in the State of Bahia Brazil. Among them, seven professionals belonged to a Medical-Surgical Clinic Unit and six from an adult Intensive Treatment Unit (ITU). As for the methodology, it was adopted the qualitative descriptive exploratory method. In what concerns data collection, it was used semi-structured interviews. Data analysis was done by using the theme content analysis technique. It is worth mentioning that, all ethical principles were respected in accordance to the Resolution 196/96 from the Brazilian Ministry of Health. Therefore, the project was formally approved by the Academic Research Ethics Committee of the Universidade Salvador by means of the Report n. 04.11.21. The interviews pointed out five categories of analysis as from the answers given by the multidisciplinary team, and four categories of analysis as from the managers side. Results indicate that, the teams differ in terms of medical board composition, but some medical specialties are alike; both managers and workers do have understanding about multidisciplinary team work for health care and its importance, they are aware that there exist advantages and difficulties for their development, and that fluent communication and interaction are important elements for hospital organizations, as well as, for their work development at this modality. It can be concluded that, the researched organizations recognize, in general terms, the work and the importance of a multidisciplinary team in a suitable organizational environment. Both teams communication and interaction were considered satisfactory. Daily observation showed that, some practices are contradictory to managers and subordinates conceptions. It was verified that, the team group join forces and communicate with fluency at the moment that they are providing service to their patients. However, it occurs a rupture in the communication fluency and at the group integration, when dealing with the multidisciplinary aspect of planning and giving continuity to the patients health care assistance.